Intelligent Leadership: Creating A Passion For Change - Hooper, Alan & Potter, John (Random House Group, 2000)
Intelligent Leadership provides an innovative analysis for managers of what makes a leader today, focusing on emotional intelligence and leadership as a psychological commitment. The need for high-quality leadership in all areas of business and organisational activity has never been greater. A myriad of interlinked factors mean that styles of leadership that were appropriate in the past are now no longer working. These factors include new technologies, more questioning attitudes to authority, the arrival of the "virtual organization" with its network of contributors, and the unprecedentedly high expectations of customers and employees. In Intelligent Leadership, Alan Hooper and John Potter look at how changes affect people in businesses and organisations, using specific case studies of individuals. They propose practical ways for leaders to provide effective leadership in a quickly changing and confusing work environment.
Keywords: Business & Economics; Management; Non-Fiction